Harmless Effect of Sulfuric Acid and Aluminum Sulfate on Barium Slag - Yanbing Chen; Zhaofeng Long; Shiyu Li; Qingguo Zeng; Haifeng Wang; Jiawei Wang (Kuangchan zonghe liyong, 2022)
Barium slag is numbered HW47 in the national hazardous waste list. At present, it is still mainly stacked, causing great environmental pollution. Aiming at this problem, the harmlessness of barium slag by sulfuric acid and aluminum sulfate was studied. The effects of excess coefficient, water amount and reaction time on the harmless effect of barium slag were investigated. The results show that, for 100 g barium slag, when the excess coefficient of aluminum sulfate was 1.5, the water volume was 25 ml, and the reaction time was 1.5 h, the concentration of Ba2+ was 93.75 mg/L and the removal rate of Ba2+ was 88.97%. When the excess coefficient of sulfuric acid was 2.0, the water volume was 25 mL, and the reaction time was 2 h, the concentration of Ba2+ was 92.30 mg/L and the removal rate of Ba2+ was 89.14%. Both of them could reach the limit of the toxicity identification standard for barium ion in GB 5085.3-2007. Under the same conditions, the treatment effect of aluminum sulfate was better than that of sulfuric acid, and the lower pH value of harmless agent was, the worse the harmless effect of barium slag was.